Alpine, Variscan, eo-Variscan belts: comparison between hot and cold orogens from the examples of French segments - Faure, Michel (Comptes Rendus. Géoscience)
The Cenozoic Alpine, and Paleozoic Variscan and eo-Variscan collisional belts are compared in the framework of the Wilson cycle considering differences between cold and hot orogens. The W. Alps result of the opening and closure of the Liguro-Piemonte ocean, whereas the Paleozoic Eo-variscan and Variscan orogenies document multiple ocean openings and collisions in space and a polyorogenic history in time. Jurassic or Early Ordovician break-up of Pangea or Pannotia megacontinents led to the formation of passive continental margins, and the opening of Liguro-Piemonte, or Rheic, Tepla-Le Conquet, and Medio-European oceans, respectively. In Paleozoic or Mesozoic, microcontinents such as Apulia and Sesia or Armorica and Saxo-Thuringia were individualized. The oceanic convergence stage was associated with the development of arcs and back-arc basins in the Variscan belt but magmatic arcs are missing in the W. Alps, and inferred in the Eo-variscan one. Though the nappe stack is mainly developed in the subducted European or Gondwana crust in the western Alps and Eo-variscan cases, the Moldanubian nappes formed in the upper plate in the Variscan case. The Alpine and Variscan metamorphic evolutions occurred under ca. 8 °C/km and 30 °C/km gradients, respectively. During the late- to post-orogenic stages, all belts experienced “unthickening” accommodated by extensional tectonics, metamorphic retrogression, and intramontane basin opening. The importance of crustal melting, represented by migmatites, granites, and hydrothermal circulations in the Variscan and Eo-Variscan belts is the major difference with the W. Alpine one. The presence, or absence, of a previous Variscan or Cadomian continental basement might have also influenced the rheological behavior of the crust.